Xerosis meter-an electro-physiological device for quick screening of dry eyes - Gupta, Y; Gupta, M; Maheshwari, R; Mittal, T (Nepalese Journal of Ophthalmology, 2010)
Aim: To study the role of ‘Xerosis Meter' in screening of dry eye cases in a large population and compare its results with Schirmer's test and tear break-up time. Materials and method: In a cross sectional study with a control group dry eye was evaluated with Xerosis Meter, Schirmer test and tear film break-up time (TBUT). Cases included in the study were divided into two groups. Group I (Control Group) comprised of asymptomatic patients while Group II (Test Group) had patients showing symptoms and signs of dry eye. The Group II was further divided into two subgroups. Group IIa had cases showing positive result with either of the two tests Schirmer test or TBUT. Group IIb had cases which showed positive results with Xerosis Meter but normal results with the other two tests. Statistics: All the observations were statistically analyzed using SPSS version 11.5 software. The results obtained were compared statistically using unpaired t-test and chi-square test. The p value of < 0.05 was considered as significant. Results: There was a statistically significant difference between the means of Xerosis Meter, Schirmer test and TBUT of the two groups: Group I and Group IIa (p value < 0.001). On comparing Group I and Group IIb the difference was found to be statistically significant with Xerosis Meter (p value < 0.001). The sensitivity and specificity of Xerosis Meter were 85.7% and 80.2% respectively. This was higher than that of the Schirmer's test (81.3% and 74.9%) and TBUT (73.2% and 68.7%). Conclusion: The "Xerosis Meter" is an effective alternate in screening of dry eye cases. It is more effective than the TBUT and as effective as the Schirmer's test in detecting both the normal and dry eye patients. DOI: 10.3126/nepjoph.v1i2.3687 Nep J Oph 2009;1(2):123-128